Posouzení technického stavu stokové sítě v obci - Shamko, Viktoryia (Vysoké učení technické v Brně. Fakulta stavební, 2021)
Bakalářská práce se zabývá posouzením stavebně-technického stavu stokové sítě ve vybrané obci. Rešeršní část je zaměřena na údržbu, druhy a četnost poruch a metody průzkumu kanalizačních objektů a úseků pro návrh rekonstrukce. Součástí práce jsou české a zahraniční metodiky vyhodnocení stavu stokové sítě. V praktické části byla provedena kamerová prohlídka vybraných úseků stokové sítě s následným zatříděním poruch a vyhodnocením dle dvou metodik. Na základě posouzení stavu jednotlivých kanalizačních úseků a šachet byla navržena sanace.

The bachelor's thesis deals with the assessment of the construction and technical condition of the sewer network in a selected village. The research part is focused on maintenance, types and frequency of failures and inspection techniques to control the condition of the sewer network and propose reconstruction. The works include czech and foreign methodologies for evaluating the condition of the sewer network. In the practical part, a camera inspection of selected sections of the sewer network was performed, followed by a defect coding and evaluation according to two methodologies. Conforming to the assessment of the condition of individual sewer sections and manholes, rehabilitation was proposed.
Assessment of the technical condition of the sewer network in the village
Keywords: Technický stav; inspekce; poruchy; stoková síť; zatřídění; vyhodnocení; Technical condition; inspection; failures; sewer network; classification; evaluation